Plan de negocios para la producción y exportación de jabones artesanales, biodegradables hechos a base de ceniza volcánica y esencias naturales hacia el mercado alemán - Ricaurte Duque, Francisco José (2019)
In human life, the execution of personal hygiene practices is of paramount importance, rather than because of its aesthetic result, because of its contribution to health. The correct cleaning of both, hands and the rest of the body reduces the possibility of contracting diseases and infections. (World Health Organization, 2012) (Importancia.org, 2018). But more than cleaning, soaps have other characteristics that help human health, as they can be exfoliants, moisturizers, among others; which contribute to the care of the skin. Germany is the country with the largest volume of toilet soap imports from the world (Trade Map, 2017), from which it can be inferred that Germany is one of the main consumers of this good, as well as that it reveals the high demand and acceptance for products coming from of the rest of the world. In the same way, the German consumer prefers to consume products that are eco-friendly (Santander Trade, 2018) that they reduce the environmental impact caused by the human presence in the world. It is for these reasons that the creation of soaps with biodegradable supplies, as well as with natural fragrances is increasing. Therefore, the ARIQ company project is born, dedicated to the production and commercialization of liquid soap, biodegradable, made with volcanic ash and natural essential oils, in a 500ml presentation where in its design it shows the beauty of the Ecuadorian volcanoes. This product is aimed at people from 31 to 65 years old of middle and upper-middle class, who live in Berlin who are looking for exotic products, and who have a pro-environmental philosophy in their lives. The general strategy of marketing that will be used is that of differentiation, which consists of highlighting the distinctive attributes of added value of the product such as artisanal processes and biodegradable inputs, as well as the unique design, emphasizing the benefits of soap to the consumer as they are its exfoliating and moisturizing action. The investment of this project is valued at 75.387,96 USD, which will be financed 33,68 percent by own capital and 66,32 percent with credit